Genetic alterations affect immune contexture of non-small cell lung cancer: Ukrainian study - Denys Kozakov; Denys Kozakov; Nazarii Kobyliak; Nazarii Kobyliak; Sofiia Livshun; Oleksii Seleznov; Oleksii Seleznov; Olena Koshyk; Olena Koshyk; Alina Matvieieva; Yaroslav Shparyk; Oleksii Kolesnik; et al. (Frontiers in Medicine)
IntroductionAlthough the role of various genetic alterations was highlighted among factors affecting the response to immunotherapy in non-small cell lung cancer (NSCLC), the relations between oncogenic driver variants and changes in the cancer immunity cycle are still unclear.AimThe study aimed to discover the links between the molecular and immune context of NSCLC.Materials and methodsThis cohort study included 254 cases of NSCLC (193 Lung Adenocarcinomas) (LUAD; 76%), and 61 squamous cell carcinomas (SCC; 24%), with pathology reports and next-generation sequencing (NGS) data available. First, the rate and spectrum of genetic alterations were assessed in the Ukrainian cohort. Second, we uncovered the relationship between the oncogenic driver mutations and PD-L1 expression in NSCLC. Finally, T-cytotoxic lymphocytes (CD8+) and tumor-associated macrophages (CD163+) were evaluated in samples with EGFR and KRAS mutations, ALK rearrangements and LUAD with no genetic findings. Immune desert, immune excluded and inflamed types of tumor immune microenvironment (TME) were defined according to the cancer immunity cycle.ResultsMore than half (52%) of the observed NSCLC cases harbored single (48.03%) or concomitant (3.94%) genetic alterations in oncogenes. The Ukrainian cohort demonstrated a high rate of EGFR (18.5%) and ALK rearrangements (9.4%) with a relatively moderate frequency of KRAS mutations (16.9%). NSCLC tumors with alterations in EGFR and ALK demonstrated a high incidence of PD-L1 expression and specific immune contexture. The number of CD8+ cells varied significantly between oncogene-driven and wild-type LUAD (p = 0.019). Non-oncogene-addicted NSCLC demonstrated the prevalence of Inflamed TME rich in CD163+ macrophages. In contrast, over half of EGFR mutant LUAD cases possessed immune desert TME type, while ALK-rearranged and KRAS mutant NSCLC showed mostly immune excluded TME.ConclusionThe high rate of PD-L1 expression in NSCLC driven by EGFR and ALK alterations was accompanied by a prevalence of low immunogenicity with a shift toward ID TME in EGFR mutant tumors and IE TME in ALK-rearranged and KRAS mutant NSCLC. Further discovery of mechanisms affecting tumor immune contexture is needed for tailoring patient management in line with particular mechanisms of immune evasion.